The effect of an overweight backpack towards comfortability and L5S1 among primary school student - Kasim, Mohd Shahir; Raja Abdullah, Raja Izamshah; Mohd Hassan, Nur Alya Syaherah; W. Mohamad, W Noor Fatihah; Mohd Shahrim, Mohammad Shah All Hafiz; Mohd Nawi, Mohd Aliff (Penerbit UniMAP, 2021)
The issue of overweight pupils’ school bag has been a subject of vast of discussion by the parents which may associate to back pain. This paper presents the effect of the weight of the backpack towards the lumbosacral joint (L5/S1) and conformability among primary student. A total of 10 respondents from the primary school students were involved in this study. Questionnaires of psychophysical experience with eight areas of body surveys were distributed as to obtain the comfortable feedback. The participants were required to perform three activities; standing without load; standing and climbing with load. The pupils are required to carry a backpack in symmetrical manner. These three activities will be recorded by using a digital camera. Due to safety measure during COVID-19 pandemic, the ImageJ Software was used to measure the joint angles and gait parameters. Based on the data measured by the software, a static and dynamic analysis were applied to calculate the torque and force for the trunk muscle, compressive and a shear force acting on the lumbosacral joint. Based on the result, It was found the student to carry 17% of their body weight, which is beyond of the 10-15% recommendation threshold. The survey shows, 40% of the students feel very uncomfortable especially at their low back, shoulder, head, and neck area due to heavy backpack. It shows the compression force on L4L5 during climbing slightly exceed the recommendation limit by NIOSH, while the others within the acceptable level. The related stakeholder should provide solutions, which conducive in order to prevent and control the occurrence of low back pain among primary student.